Milk Market Research In The Member States of The European Union - Violeta GAGU (LEOCĂ); Gheorghe Adrian ZUGRAVU; Mirela Gianina CALU (Communications of International Proceedings, 2021)
The change in consumer preferences for dairy products is due to diversified production as well as socio-economic development through the evolution of the global and European markets. European policies, reforms influence the dairy sector and facilitate the connection with the markets. The paper proposes a presentation and analysis of the milk market in the Member States of the European Union as aimed at ensuring food security.
Keywords: The milk market; EU milk production; price policy